Regulation of phosphatidylcholine-hydrolizing phospholipase C activity under the influence of biotic stress effectors in plants - Pokotylo, I.V.; Martinec, J.; Kravets, V. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
The influence of biotic stress effectors on the activity of phosphatidylcholine-hydrolizing phospholipase C (PC-PLC) in tobacco suspension cell culture and the level of PC-PLC genes expression in Arabidopsis has been demonstrated. A decrease in the level of diacylglycerol second messenger production by PC-PLC has been detected in response to the treatment with either salicylic acid or elicitors (lipopolysaccharides and benzotiadiazol). The treatment with methyl jasmonate has not influenced the activity of PC-PLC. An implication of PC-PLC to the mechanisms of biotic stress effectors action has been disclosed on the levels of changes to enzymatic activity of PC-PLC and gene expression of PC-PLC.